2022
DOI: 10.1007/s00167-021-06846-8
|View full text |Cite
|
Sign up to set email alerts
|

Mid-flexion laxity could be identified with continuous flexion-arc gap assessment in patients with a large preoperative convergence angle

Abstract: PurposeTo analyze the incidence of intraoperative mid‐flexion laxity using continuous flexion‐arc gap assessment, risk factors for mid‐flexion laxity, and clinical results in navigation‐assisted total knee arthroplasty (TKA). MethodsNinety posterior‐stabilized TKAs were performed under navigation guidance for patients with degenerative arthritis and varus deformity. Intraoperatively, the gap between the trial femoral component and insert was evaluated in the navigation system with continuous flexion‐arc gap as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Second, a hybrid cementation was performed which could lead to potentially worse radiological results. However, recent studies found similar results between hybrid and full cementation TKA at long‐term follow‐up [4, 35]. Furthermore, all tibial components were cemented, and loosening was always observed on the tibial component in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…Second, a hybrid cementation was performed which could lead to potentially worse radiological results. However, recent studies found similar results between hybrid and full cementation TKA at long‐term follow‐up [4, 35]. Furthermore, all tibial components were cemented, and loosening was always observed on the tibial component in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…Finally, previous research that has modelled radiostereometric analyses of the anterior‐posterior translation of TKA designs during sit‐to‐stand and deep knee lunges reported translations of 6.8‐9.9 mm, suggesting that activities which require higher degrees of flexion may result in translations >7 mm [28]. As a result, radiographic evaluation of the flexion‐arc gap throughout the knee's range of motion may be a more clinically appropriate and effective method of assessing mid‐flexion laxity [29].…”
Section: Discussionmentioning
confidence: 99%
“…A continuous radiological image study indicated that a small intercomponent distance of less than 2 mm does not result in lift-of phenomena or clinical patient discomfort [12]. While there is no conclusive evidence deining a permissible range for clinical outcomes, surgeons generally aim for less than 3 mm of component gap mismatch in the mid-lexion range after TKA [19]. The clinical relevance of 1.0 to 1.1 mm in postrelease mismatch reduction may be seen in the current cohort, where component gap mismatch in the mid-lexion range was reduced to a mean of 1.0 mm and 1.1 mm, such that 95% and 90% of the cases came to within the Posterior capsular release is recognized as an efective surgical method for addressing lexion contracture in TKA.…”
Section: Discussionmentioning
confidence: 99%